Design of an Indicator System for the Evaluation and Selection of Applications for People With Autistic Spectrum Disorder - Gallardo-Montes, Carmen del Pilar; Caurcel-Cara, María Jesús; Rodríguez-Fuentes, Antonio (Revista Electrónica Educare, 2021)
Objective: Information and communication technologies (ICT) provide people with autism spectrum disorder (ASD) with a wide range of possibilities for development. At the same time, there are numerous applications (apps) aimed at children with autism; so, this proposal aims to offer a list of validated indicators that analyze the strengths and weaknesses of these apps. Methodology: The exhaustive analysis of previous studies has allowed the creation of this instrument in relation to the design of the app, its content, and its pedagogical aspects. According to its clarity, coherence, relevance, and objectivity, the system of indicators was validated through an instrumental study of content validity, applying the method of expert and judges’ judgment. Results: A total of 12 judges scored each of the designed indicators and sub-indicators as good to excellent, with excellent Intraclass Correlation coefficients, significant and strong Kendall’s W inter-judge agreement, and high levels of internal consistency. It was found to be a valid and reliable instrument. Discussion: The positive results derived from the validation of the instrument have resulted in a system of indicators composed of desirable criteria for an app for people with ASD. ASD specialists and family members will have an intuitive tool for the selection of apps adapted to the needs of this group, covering different parameters.